2021
DOI: 10.3390/ijerph18179240
|View full text |Cite
|
Sign up to set email alerts
|

Proverbs and Aphorisms in Neurorehabilitation: A Literature Review

Abstract: Introduction: Brain plasticity is not limited to childhood or adolescence, as originally assumed, but continues into adulthood. Understanding this conceptual evolution about the nervous system, neuroscience and neurorehabilitation, researchers have left different proverbs and aphorisms derived of their investigations that are still used in university and postgraduate training. A proverb is defined as a phrase of popular origin traditionally repeated invariably, in which a moral thought, advice or teaching is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…He used this term as the title of his collection of sayings, in which he set out some medical principles ( Hippocrates, 1994 ). During the 19th, 20th, and 21st centuries, several authors in the medical field developed As related to neuroscience and neurorehabilitation that helped to improve our understanding of the nervous system and, therefore, the management of the neurological patient ( Cano-de-la-Cuerda, 2021 ). Medical As are recognised as educating for narrative sensitivity, as a help to memorise instructions, to inform the patient about clinical judgement, to reinforce the physician’s professional behaviour, and to build the physician’s professional identity ( Levine and Bleakley, 2012 ).…”
Section: Paroemias: History and Goals Of Proverbs And Aphorismsmentioning
confidence: 99%
“…He used this term as the title of his collection of sayings, in which he set out some medical principles ( Hippocrates, 1994 ). During the 19th, 20th, and 21st centuries, several authors in the medical field developed As related to neuroscience and neurorehabilitation that helped to improve our understanding of the nervous system and, therefore, the management of the neurological patient ( Cano-de-la-Cuerda, 2021 ). Medical As are recognised as educating for narrative sensitivity, as a help to memorise instructions, to inform the patient about clinical judgement, to reinforce the physician’s professional behaviour, and to build the physician’s professional identity ( Levine and Bleakley, 2012 ).…”
Section: Paroemias: History and Goals Of Proverbs And Aphorismsmentioning
confidence: 99%
“…Jamie L. Rehmel [15] analyzed and tested the cognition of proverbs from the perspective of brain function and pathology. Roberto Cano-de-la-Cuerda [16] used proverbs related to neuroscience and neurological rehabilitation to help understand the nervous system and provide methods and techniques for the rehabilitation of neurological patients. From the perspective of neuroscience, Kljajevic, V [17] took 333 healthy individuals aged 18 ∼ 89 years as samples and found that age had a significant impact on the interpretation of proverbs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specific rehabilitation issues, including comprehensive cardiovascular rehabilitation ( 3 ) and the conceptual evolution of neurorehabilitation ( 4 );…”
Section: Introductionmentioning
confidence: 99%